Transformasi Pendidikan pada Pandemi Covid-19 di Sekolah Dasar - Bambang Sapudjo (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This article is motivated by changes in the way of life of people around the world, especially in Indonesia. One of the changes is in the field of education so that transformation or renewal is needed in the education system to be applied during the current pandemic conditions. Because there are so many cases regarding the world of education that are getting worse even though we use technology that is quite advanced, this is what we need to understand together. This study aims to describe the changes that occur in elementary schools and how teachers can overcome them. The data obtained were qualitative data containing descriptions of the results of learning observations and teacher interviews regarding changes that occurred at SD N 03 Sengare, Pekalongan. Based on the results of the interview, learning activities using online mode at SDN 03 Sengare are still not fully effective because not all students there can connect to the internet and there is a lack of available communication tools, but some teachers can neutralize this in various ways that can be done.